Did the Minimum Wage Reduce the Gender Wage Gap in Germany? - Marco Caliendo; Linda Wittbrodt (Institute of Labor Economics (IZA), 2021)
In many countries, women are over-represented among low-wage employees, which is why a wage floor could benefit them particularly. Following this notion, we analyse the impact of the German minimum wage introduction in 2015 on the gender wage gap. Germany poses an interesting case study in this context, since it has a rather high gender wage gap and set the minimum wage at a relatively high level, affecting more than four million employees. Based on individual data from the Structure of Earnings Survey, containing information for over one million employees working in 60,000 firms, we use a difference-in-difference framework that exploits regional differences in the bite of the minimum wage. We find a significant negative effect of the minimum wage on the regional gender wage gap. Between 2014 and 2018, the gap at the 10th percentile of the wage distribution was reduced by 4.6 percentage points (or 32%) in regions that were strongly affected by the minimum wage compared to less affected regions. For the gap at the 25th percentile, the effect still amounted to -18%, while for the mean it was smaller (-11%) and not particularly robust. We thus find that the minimum wage can indeed reduce gender wage disparities. While the effect is highest for the low-paid, it also reaches up into higher parts of the wage distribution.
Keywords: J16; J31; J38; J71; 330; minimum wage; gender wage gap; regional bite